Data protection about children on the Internet (International Journal of Contemporary Security Studies, 2023)
Digitization of data has facilitated everyday communication and data exchange, accelerated business, but has also enabled different forms of data abuse in cyberspace. Malicious subjects can easily, by using new technologies, come into possession of various data about Internet users. The data they mainly access is ussualy collected without the knowledge of the users. Perpertrators often use insufficient information of the users about potential dangers on the Internet. Children spend a large part of their time on the Internet, but they usually are not aware of dangers they can come across while using the Internet, so they often leave there information and content that can easily be misused. An additional danger for children on the Internet is the possibility of sexual exploitation. In addition, there is more and more peer violence on the Internet, which creates special psychological and social problems for children. Since children do not have enough life experience, it is necessary to take measures and activities to protect their data on the Internet. The parents have most important role, then an educational institutions where children stay, but the legal regulation of the protection of data about children on the Internet is also of great importance.
Keywords: children, internet, personal data, parental control, educational institutions, legal regulations